“CHRIST CONSUMES THE MARROW OUT OF OUR BONES” – CORPOREALITY IN THE MYSTICAL DOCTRINE OF JOHN OF RUUSBROEC (*1293 – †1381) - Michel Kors (Perspectiva Teológica, 2020)
In this article we pretend to explore the theme of corporeality in the mystical doctrine of the medieval author John of Ruusbroec. After explaining the radically different understanding of a body in medieval thinking we present a theoretical framework based on Patricia Dailey’s analysis of the inner and the outer body. After this, we make a first analysis of Ruusbroec’s approach to the body in het mystical experience. In Ruusbroec’s work the integration of the inner and outer body is more evident than in the previous tradition, that is, especially in the female spirituality of the 13th century. Corporeality is a theme with limited occurrence in Ruusbroec’s mystical doctrine, and it is mainly linked to Eucharistic devotion, but not exclusively.